Identifying Risk-Free Asset Proxies in Companies Listed on the Indonesia Stock Exchange from 2017 to 2023 Using the Zero-Beta Capital Asset Pricing Model - Ghazali, Fajri Alan, Mr.; Suardi, Lenny, Mrs. (UI Scholars Hub, 2026)
This study evaluates Bank Indonesia Certificates (SBI), IndONIA, and gold as zero-beta proxies for Indonesian equities. Using daily returns for 213 firms listed on the Indonesia Stock Exchange (2017–2023) and the Jakarta Composite Index as the market return, we estimate firm-level zero-beta CAPMs and compute Wald statistics test to identify the appropriate risk- free asset proxy for each individual company; and firm-level outcomes are then aggregated under a Bernoulli/Binomial criterion with a 95% threshold. Empirical results show that gold satisfies the zero-beta condition for 207 of 213 firms (97.18%), whereas SBI and IndONIA satisfy it for five (2.35%) and six (2.82%) firms, respectively. The findings indicate that, despite nonzero variance, gold behaves as a zero-beta asset for Indonesian equities during 2017–2023; practitioners may consider gold as an alternative risk-free proxy in CAPM applications, while noting limitations related to daily data frequency, exchange-rate influences, and the need for robustness checks.